2013
DOI: 10.1016/j.jinorgbio.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Metal toxicity and opportunistic binding of Pb2+ in proteins

Abstract: Lead toxicity is associated with various human diseases. While Ca2+ binding proteins such as calmodulin (CaM) are often reported to be molecular targets for Pb2+-binding and lead toxicity, the effect of Pb2+ on the Ca2+/CaM regulated biological activities cannot be described by the primary mechanism of ionic displacement (e.g., ionic mimicry). The focus of this study was to investigate the mechanism of lead toxicity through binding differences between Ca2+ and Pb2+ for CaM, an essential intracellular trigger p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…If this latter hypothesis were correct, it would help to explain the biphasic response of CaM activation to Pb 2+ , where trace concentrations can activate the protein, which is subsequently deactivated with increasing concentration. The study further noted that Pb 2+ did not produce conformational changes when Pb 2+ was introduced to Ca 2+ -loaded CaM, despite differences in binding affinity values, which suggests that Pb 2+ either displaces Ca 2+ without disrupting the structure, or Pb 2+ fails to displace Ca 2+ , but can deactivate the protein through opportunistic binding in a secondary site (123). In the latter case, it is possible that Pb 2+ may bind opportunistically to regions of the protein outside of the normal metal binding sites, such as the carboxyl-rich central helix of CaM (Fig.…”
Section: Nmr/binding Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…If this latter hypothesis were correct, it would help to explain the biphasic response of CaM activation to Pb 2+ , where trace concentrations can activate the protein, which is subsequently deactivated with increasing concentration. The study further noted that Pb 2+ did not produce conformational changes when Pb 2+ was introduced to Ca 2+ -loaded CaM, despite differences in binding affinity values, which suggests that Pb 2+ either displaces Ca 2+ without disrupting the structure, or Pb 2+ fails to displace Ca 2+ , but can deactivate the protein through opportunistic binding in a secondary site (123). In the latter case, it is possible that Pb 2+ may bind opportunistically to regions of the protein outside of the normal metal binding sites, such as the carboxyl-rich central helix of CaM (Fig.…”
Section: Nmr/binding Studiesmentioning
confidence: 95%
“…The compact folding observed in the crystalline structure of Pb 2+ -bound CaM suggested a potential allosteric binding site for Pb 2+ in this region, and results of structural analyses identified the carboxyl-rich region from residues 78–84 as a strong candidate for binding of Pb 2+ (Fig. 2A) (123). …”
Section: Structural Analysis Of Pb2+ Vs Ca2+ Binding Sitesmentioning
confidence: 99%
“…To address these questions, a follow-up study was conducted that compared structural differences and binding affinities for Pb 2+ and Ca 2+ bound to CaM [84] . [85,86] , and with a related study by Dowd et al which reported that occupancy of Pb 2+ in Ca 2+ -binding sites may activate a protein, mimicking the presence of Ca 2+ , but may also result in a more compact conformation of the protein [87] .…”
Section: + Toxicitymentioning
confidence: 99%
“…These results suggest that, at lower concentrations, Pb 2+ mimics Ca 2+ by ionic replacement in structured Ca 2+ -binding sites, which would inappropriately activate the protein. Conversely, at higher concentrations, Pb 2+ appears to interact with CaM through a different mechanism involving opportunistic binding outside of the known Ca 2+ -binding sites, or in auxiliary binding sites for Zn 2+ and Mg 2+ , resulting in allosteric inhibition of protein activity [84] . Thus, CaM likely represents an important participant in Pb 2+ neurotoxicity across a range of Pb 2+ concentrations, and due to its ubiquitous presence across a multitude of functions regulated by the Ca 2+ -signaling network.…”
Section: Nmda Receptormentioning
confidence: 99%
“…It is one of the non-essential elements with no role in human metabolism, with children being more affected than adults [59]. Lead replaces calcium in bones and weakens bone structure and replaces Zn, blocking oxygen exchange in red blood cells.…”
Section: Environmental Pollution and Healthmentioning
confidence: 99%